FACEBOOK, CYBERSPACE, AND IDENTITY - Olivier, Bert (PINS-Psychology in Society, 2025)
In this article the use of the social networking site, Facebook, is scrutinized in the light of Turkle’s work on identity in relation to the internet, as well as of commentaries regarding the growing popularity of the social networking site. The related issue of panopticism regarding sites such as Facebook is examined in the light of the work of Foucault on disciplinary mechanisms in modern society. Virilio gives greater insight on the question of the social consequences of cyberspace as the new “frontier”, and focuses on the decline of language in favour of the growing dominance of images in cyber-domains like Facebook. These findings are finally interpreted with regard to “identity” in terms of Lacan’s conception of the subject.